Sensitive determination of ciprofloxacin and norfloxacin in biological fluids using an enzymatic rotating biosensor - Torriero, Angel Alberto Jesus (2006)
The high sensitivity that can be attained using an enzymatic system and mediated by catechol has been verified by on-line interfacing of a rotating biosensor and continuous-flow/stopped-flow/continuous-flow processing. Horseradish peroxidase, HRP, [EC 1.11.1.7], immobilized on a rotating disk, in the presence of hydrogen peroxide catalyzed the oxidation of catechol, whose back electrochemical reduction was detected on glassy carbon electrode surface at −200mV. Thus, when ciprofloxacin (CF) or norfloxacin (NF) was added to the solution, these piperazine-containing compounds participate in Michael addition reactions with catechol to form the corresponding aminoquinone derivative, decreasing the peak current obtained in proportion with the increase of its concentration. CFwas used as the model piperazine-containing compound for the study. The influenceof indicator composition on the nature of the analytical response has been assessed through examining the electrochemical properties of three derivatives. Interference by electroactive species (ascorbate, urate, and tyrosine) and other physiological constituents (cysteine, glutathione) has also been assessed.